A Novel 4D Ultrasound Parenting Intervention for Substance Using Pregnant Women in Finland: Participation in Obstetric Care, Fetal Drug Exposure, and Perinatal Outcomes in a Randomized Controlled Trial - Heidi Jussila; Marjukka Pajulo; Eeva Ekholm (Springer New York LLC, 2022)
Objectives: The aim of the study was to explore the effect of a new prenatal intervention on participation in obstetric care, fetal drug exposure, and perinatal outcomes among substance using pregnant women in Finland.
Methods:The participants were 90 women referred to a hospital obstetric outpatient clinic due to current or recent substance use. The intervention group (n = 46) was offered three interactive ultrasounds at 24, 30 and 34 gestational weeks and a pregnancy diary accompanied by three prenatal infant mental health consultations. The intervention elements were designed to enhance parental mentalization and prenatal attachment. A randomized control group (n = 44) design was used. All participants were offered treatment-as-usual in the obstetric tertiary setting. Medical record data and meconium toxicology were analyzed.
Results:The retention rate in the whole sample was 89%. Retention was higher in the intervention group (96% vs. 82%, p < 0.05), of which 74% attended all three ultrasound sessions. However, the pregnant women in the intervention group participated less often in all the scheduled obstetric standard care visits (59% vs. 83%, p = 0.02). Fetal drug exposure and perinatal outcomes were similar in both groups. Within the whole sample, 13% of the neonates were preterm, 12% small for gestational age and 7% had exposure to drugs.
Conclusions for Practice: Retention in the intervention was very good. Watching the fetus with parenting focus seemed to motivate these high-risk women. Interestingly, the pregnant women in the intervention group tended to prefer the intervention sessions to the routine care. Clinical implications of this finding are discussed.
Trial Registry: The trial registration number in ClinicalTrials.gov: NCT03413631.